2019
DOI: 10.1021/acsami.9b01196
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening for Advanced Thermoelectric Materials: Diamond-Like ABX2 Compounds

Abstract: High-throughput (HTP) calculations are a highly promising direction for the discovery of novel functional materials. Here we use an HTP framework to investigate the electronic structures and p-type thermoelectric properties of the ABX2 compounds with diamond-like structures. We show application of HTP both to identify compounds and also to identify underlying trends. A total of 65 entries out of 84 908 in the Materials Informatics Platform are selected for this study. The electronic structures and chemical-bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 60 publications
1
78
0
Order By: Relevance
“…Due to the record-breaking high-temperature ZT of SnS, the Te-free Sn(S, Se) alloys are of particular interest, and experimental studies have demonstrated a reduction in the thermal conductivity of mixed compositions [12,14].Thermoelectricity is unique in that all four of the terms in the figure of merit ZT are amenable to calculation using first-principles electronic-structure methods such as density-functional theory (DFT) [18]. There have been a number of theoretical studies on existing and potential new single-component bulk thermoelectrics [6,[19][20][21][22][23], and there have recently been efforts to use high-throughput modelling to screen large numbers of compounds in a bid to identify new candidate thermoelectrics [24,25].Studying multicomponent alloy systems with first-principles methods is challenging, however, as building a realistic model requires calculations on a large number of configurations that for complex systems with lowsymmetry unit cells can easily approach the cost of a screening study [26]. Ektarawong and Alling used a firstprinciples cluster expansion method to study the Pnma Sn(S 1-x Se x ) system and confirmed the stability of the mixed phases at finite temperature [27].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the record-breaking high-temperature ZT of SnS, the Te-free Sn(S, Se) alloys are of particular interest, and experimental studies have demonstrated a reduction in the thermal conductivity of mixed compositions [12,14].Thermoelectricity is unique in that all four of the terms in the figure of merit ZT are amenable to calculation using first-principles electronic-structure methods such as density-functional theory (DFT) [18]. There have been a number of theoretical studies on existing and potential new single-component bulk thermoelectrics [6,[19][20][21][22][23], and there have recently been efforts to use high-throughput modelling to screen large numbers of compounds in a bid to identify new candidate thermoelectrics [24,25].Studying multicomponent alloy systems with first-principles methods is challenging, however, as building a realistic model requires calculations on a large number of configurations that for complex systems with lowsymmetry unit cells can easily approach the cost of a screening study [26]. Ektarawong and Alling used a firstprinciples cluster expansion method to study the Pnma Sn(S 1-x Se x ) system and confirmed the stability of the mixed phases at finite temperature [27].…”
mentioning
confidence: 99%
“…Thermoelectricity is unique in that all four of the terms in the figure of merit ZT are amenable to calculation using first-principles electronic-structure methods such as density-functional theory (DFT) [18]. There have been a number of theoretical studies on existing and potential new single-component bulk thermoelectrics [6,[19][20][21][22][23], and there have recently been efforts to use high-throughput modelling to screen large numbers of compounds in a bid to identify new candidate thermoelectrics [24,25].…”
mentioning
confidence: 99%
“…1a). The original 158 entries of chalcogenides and pnictides are quoted from our previous HTP works and referred in the DFT database later 10,11 . By exhausting all the possible combinations among the aforementioned cations and anions, we construct a search space of diamond-like compounds with 482 entries (158 DFT calculated and 324 uncalculated) 10 .…”
Section: Data Sourcementioning
confidence: 99%
“…In 2018, Xi et al applied HTP ab initio calculation to 161 ptype chalcogenides and experimentally verified the recommended TE compound Cd 2 Cu 3 In 3 Te 8 with ZT >1.0 10 . Li et al studied both p-type pnictides and chalcogenides in the atomic ratio 1:1:2, and pnictides showed exceptionally high power factors (PFs) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…An implication is that thermoelectricity is a particularly rich area for testing and demonstrating theory based materials search strategies. [18][19][20][21][22] Here we report and demonstrate a high throughput strategy that starts with a simple electronic structure based metric. Application to a set of half-Heusler compounds identifies previously known high performance materials.…”
Section: Introductionmentioning
confidence: 99%